Accumulation of neurofibrillary tangles and activated microglia is associated with lower neuron densities in the aphasic variant of Alzheimer's disease. (5th November 2020) - Ohm, Daniel T.; Fought, Angela J.; Martersteck, Adam; Coventry, Christina; Sridhar, Jaiashre; Gefen, Tamar; Weintraub, Sandra; Bigio, Eileen; Mesulam, M.‐Marsel; Rogalski, Emily; Geula, Changiz
Abstract: The neurofibrillary tangles (NFT) and amyloid‐ß plaques (AP) that comprise Alzheimer's disease (AD) neuropathology are associated with neurodegeneration and microglial activation. Activated microglia exist on a dynamic spectrum of morphologic subtypes that include resting, surveillant microglia capable of converting to activated, hypertrophic microglia closely linked to neuroinflammatory processes and AD neuropathology in amnestic AD. However, quantitative analyses of microglial subtypes and neurons are lacking in non‐amnestic clinical AD variants, including primary progressive aphasia (PPA‐AD). PPA‐AD is a language disorder characterized by cortical atrophy and NFT densities concentrated to the language‐dominant hemisphere. Here, a stereologic investigation of five PPA‐AD participants determined the densities and distributions of neurons and microglial subtypes to examine how cellular changes relate to AD neuropathology and may contribute to cortical atrophy. Adjacent series of sections were immunostained for neurons (NeuN) and microglia (HLA‐DR) from bilateral language and non‐language regions where in vivo cortical atrophy and Thioflavin‐S‐positive APs and NFTs were previously quantified. NeuN‐positive neurons and morphologic subtypes of HLA‐DR‐positive microglia (i.e., resting [ramified] microglia and activated [hypertrophic] microglia) were quantified using unbiased stereology. Relationships between neurons, microglia, AD neuropathology, and cortical atrophy were determined using linear mixed models. NFT densities were positively associated with hypertrophic microglia densities ( P  < 0.01) and inversely related to neuron densities ( P  = 0.01). Hypertrophic microglia densities were inversely related to densities of neurons ( P  < 0.01) and ramified microglia ( P  < 0.01). Ramified microglia densities were positively associated with neuron densities ( P  = 0.02) and inversely related to cortical atrophy ( P  = 0.03). Our findings provide converging evidence of divergent roles for microglial subtypes in patterns of neurodegeneration, which includes hypertrophic microglia likely driving a neuroinflammatory response more sensitive to NFTs than APs in PPA‐AD. Moreover, the accumulation of both NFTs and activated hypertrophic microglia in association with low neuron densities suggest they may collectively contribute to focal neurodegeneration characteristic of PPA‐AD. Abstract : Quantitative analyses of microglial subtypes and neurons are lacking in non‐amnestic clinical Alzheimer's disease (AD) variants, including primary progressive aphasia (PPA‐AD). Our findings provide converging evidence of divergent roles for microglial subtypes in patterns of neurodegeneration, which includes hypertrophic microglia likely driving a neuroinflammatory response more sensitive to neurofibrillary tangles than amyloid‐beta plaques in PPA‐AD. Moreover, the accumulation of both neurofibrillary tangles and activated hypertrophic microglia in association with low neuron densities suggest they may collectively contribute to focal neurodegeneration characteristic of PPA‐AD.